Peningkatan Fungsi Kognitif Klien dengan Isolasi Sosial yang Mendapatkan Latihan Keterampilan Sosial: Literature Review - Suyatno Suyatno; Hamid Yani S. Achir (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2019)
Social Skills Training (SST) is one of the interventions aimed at improving communication and providing new skills to schizophrenic clients with social isolation problems. SST is specifically carried out on clients with social isolation experiencing a decrease number, frequency and quality of social contacts; endurance of contact and negativism are associated with feelings of isolated. SST is performed through several sessions. Each session consisted of several sections such as modeling, role playing, performance feedback and transfer training. The stages in the SST not only focus on social skills, but also cognitive functions. SST can be applied to healthy and disturbed clients, children as well as adults. Method: Literature review is based on issues, methodologies, equations and advanced research proposals. There are 5 quantitative studies and 1 bulletin. Out of Five studies conducted, one study on healthy clients and 4 disturbed clients. such as autism, high risk, and cognitive impairment.